2013
DOI: 10.1007/s13595-013-0299-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between density and aesthetic attributes of wood and preference of Malagasy consumers

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 12 publications
0
25
1
Order By: Relevance
“…Future work might consider the comparison of differently coloured species while examining appreciation and preferences among consumers. Ramananantoandro et al (2013) measured colour (CIEL*a*b*), texture and density and revealed preferences for darker and yellowish wood surfaces among Antananarivo consumers in the case of a range of 12 species with yellow to red, light to dark, textured and non-textured surfaces used for furniture.…”
Section: Discussionmentioning
confidence: 99%
“…Future work might consider the comparison of differently coloured species while examining appreciation and preferences among consumers. Ramananantoandro et al (2013) measured colour (CIEL*a*b*), texture and density and revealed preferences for darker and yellowish wood surfaces among Antananarivo consumers in the case of a range of 12 species with yellow to red, light to dark, textured and non-textured surfaces used for furniture.…”
Section: Discussionmentioning
confidence: 99%
“…These defects are in direct relation to surface functionality (De Moura 2006). In order to assess the quality of a wood machined surface, two sets of criteria are generally used: those linked to geometry and those related to the physics and chemistry of the surface (Gurau 2007;Rajemison 2013).…”
Section: Surface Qualitymentioning
confidence: 99%
“…Commonly-used criteria defined in the standard are raised grain, fuzzy grain, torn grain and chip marks (Goli 2003). Some authors have also used machining traces and splinter occurrence at the end of the wooden piece (Khazaeian 2006;Rajemison 2013). The disadvantage of this surface assessment comes from its subjectivity, because it is fully dependent on the assessor's perception (Marchal and Mothe 1994;Scholz et al 2007).…”
Section: Geometrical Characterisation Of Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…As found by Marchal and Mothe (1994) in France, diverging preferences could be identified where one group preferred clear surfaces and another group preferred slightly knotty surfaces (small knots). From a preference study of Malagasy consumers, Ramananantoandro et al (2013) conclude that aesthetic features like colour and texture and the density of furniture wood species have an effect on consumers' preferences. Hoibo and Nyrud (2010) suppose harmonious and homogeneous surfaces are preferred by consumers which are achieved with few knots and even knot patterns in visual product surfaces.…”
mentioning
confidence: 99%